RANCANG BANGUN APLIKASI PENENTUAN LETAK BARANG PADA TOKO PREMBUN DENGAN METODE ASSOCIATION RULE DATA MINING - Kusuma Satria, Hafiyan Nafan; Zuliarso, Eri (Information Technology and Telematics, 2018)
Abstract - The problems that occur in the Prembun Store are related to the arrangement of the goods, so far, the arrangement of the items in the Prembun Shop uses the rules of arrangement based on the type of goods, size, and characteristics of the goods. Item position regulation The Prembun store only uses management subjectivity in arranging goods in the store and has not seen in terms of consumer behavior. Another problem is that there are two types of items based on chemical properties that cannot be brought close to the raw food and insect drugs. Then the arrangement of goods is still not neat. Whereas shop layout that is neatly structured and oriented to consumer desires can be a plus for the store to attract consumer shopping. The association rule method is one of the main techniques in data mining and is the most commonly used form of finding patterns or patterns of a data set. The design of the application to determine the location in the Prembun Store with the data mining rule association method is a search system that contains processing data from transactions, then look for relationships between the items they lead. This information can provide additional information for Prembun Stores in retrieval of results to determine the location items on the Prembun Store shelf.